Does Economic Integration Affect the Structure of Industries? Empirical Evidence from the CEE - D'Artis Kancs (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2007)
In this paper we study how European integration would affect the industry location and sectoral specialisation of local economies in the CEE accession countries. The theoretical framework of our study is based on the new eco- nomic geography, which allows us to predict not only the post-integration spe- cialisation patterns, but captures also other general equilibrium effects, such as transition to market economy, which turn out to be highly significant in CEE. Our empirical results suggest that the CEE specialisation pattern would be distinct from the old EU member states. First, the EU integration would reduce regional specialisation in CEE. Second, the bell-shaped specialisation pattern predicted by the underlying theoretical framework is inverse in CEE. We could explain a large portion of these differences by CEE-specific processes, such as integration of the CMEA. These distortions are higher in those regions, which were more integrated in the CMEA. Our simulation results also suggest a convergence in the specialisation across the CEE regions.
Keywords: F15; R12; R13; 330; Economic geography; transport costs; European integration; monop- olistic competition.; Wirtschaftsintegration; Industriestruktur; Regionale Arbeitsteilung; Osteuropa